Theoretical and methodological approaches to evaluating the effectiveness marketing of enterprises - Меленчук, Юлія Тарасівна (Technology audit and production reserves, 2015)
The market economy environment in our country gave rise to business planning and marketing planning at enterprises. The evaluation of financial and performance indicators is quite common in Ukrainian enterprises, but the evaluation of the effectiveness of such areas as marketing, human resources and intangible assets is significantly less developed. The article is devoted to defining the essence of marketing costs and the approaches to evaluating their effectiveness. The marketing costs from the standpoint of marketing investments are determined. Since the purpose of any business is profit making, we consider marketing budget (cost) the investments, means that the evaluation of the ROI of marketing investment is a key indicator of marketing. The concept of the effectiveness of marketing activities is developed, as well as the methodological approaches to evaluating such activity. The analysis of the marketing plan allows manager to evaluate the effectiveness of the work done in general; to identify those activities that bring tangible results; to identify programs for which funds have been spent, but because of certain factors, they were not effective; to realize the big picture of the company and outline future strategy. This demonstrates the need for continuous and comprehensive evaluation of the effectiveness of marketing activities.